FEATURES OF HISTORICISM IN THE ARCHITECTURE OF EARLY 20TH CENTURY MOSQUES IN THE RUSSIAN EMPIRE - Tortsova Olga Yu. (Архитектон, 2022)
This article is devoted to the architecture of a small group of mosques built in the Russian Empire in the early 20th century. This group consists of three mosques: the 1906 mosque in Tver, the 1908 mosque in Vladikavkaz, and the 1916 mosque in St. Petersburg. The common feature of these mosques is their décor that shows that the architects drew on the historical architectural styles of Muslim countries. References to historicism in the architecture of Russian mosques are considered as part of the pan-European process of deciding how to approach Muslim religious architecture. Possible sources of architectural form and décor citations in Russian mosques and reasons for referring to certain architectural traditions are identified. Emphasis is made on the architecture of the mosque façades considering the limited scope of the article and the fact that detailed drawings for the original interior décor of the mosques in Vladikavkaz and Tver are not available, and it would be rather difficult to recreate their interiors. The study aims to show the specific features of historicism in the architecture of Russian mosques and the evolutionary pathways of this style that were emerging in the early 20th century (interrupted by the 1917 revolution).